A triphenylene-based conjugated microporous polymer: construction, gas adsorption, and fluorescence detection properties1. Issue 20 (6th March 2015) - Han, Jie; Fan, Xia; Zhuang, Zhan-Zhong; Song, Wei-Chao; Chang, Ze; Zhang, Ying-Hui; Bu, Xian-He
<x xml:space="preserve">Abstract</x> A conjugated microporous triphenylene-based polymer has been synthesized and characterized with high CO2 and H2 adsorption as well as fluorescent response to nitrobenzene.